Gestation Period and Its Bio-Psychosocial and Economic Factors Analysis on Toddler Growth and Development - Nicky Danur Jayanti; Senditya Indah Mayasari (Journal of Ners and Midwifery, 2021)
The growth and development of toddlers is influenced by hereditary and environmental factors. Genetic factors, biologically have strong influences on toddlers’ growth in their early years of life. While psychologically, a good interpersonal relation of pregnant women with their families will make them more ready to undergo the pregnancy and childbirth. On the other hand, socially, the level of parental education might affect the nutrition intake and parenting patterns. For the economic factor, the level of family income and their ability to provide sufficient nutrition input might affect the nutritional status during gestation. The nutrition input during pregnancy highly contributes to the fetus growth and development. A poor nutrition input during gestation might cause an Intrauterine Growth Retardation (IUGR) and growth and development disorder. This study aimed to analyze the bio-psychosocial and economic factors of gestation period on toddler growth and development. This is a correlational analytic study with 80 mothers and toddlers as the sample. The data was analysed using univariat, bivariate with Chi square and multivariate with logistic regression. The results show that the statistically significant independent variables which influence the growth and development of toddlers are the mother height (p = 0.001), LILA (p = 0.008), family income (p = 0.007), infant birth weight (p = 0.009) and family support (p = 0.013). While the statistically insignificant independent variable is the mother level of education (p = 0.086).